Experimental investigation on partial replacement of steel slag and E-waste as fine and coarse aggregate. (2021) - Bharani, S.; Rameshkumar, G.; Manikandan, J.; Balayogi, T.; Gokul, M.; Bhuvanesh, D.C.
Abstract: The wastes from the industries are the major problem in present condition. The recycling of all waste using recycling unit is economically facing many problems. The main objectives of this study is the partial replacement of Steel slag and E-waste from the industrials to find the mechanical strength of concrete. Four mixes with different mix proportion is obtained to find the properties which includes compressive, split tensile and Flexural strength of concrete. The partial replacement of M- sand by steel slag with 10%, 20% and 30% to find the optimum percentage of replacement. Using optimum percentage as constant, the Coarse Aggregate is replaced with certain percentage by E-Waste.